2017
DOI: 10.1038/leu.2016.385
|View full text |Cite
|
Sign up to set email alerts
|

Soluble programmed death-ligand 1 as a prognostic biomarker for overall survival in patients with diffuse large B-cell lymphoma: a replication study and combined analysis of 508 patients

Abstract: International audienceDiffuse large B-cell lymphoma (DLBCL) is an aggressive hematologic malignancy with more than two-thirds of the patients cured with first-line rituximab-based treatments. However, relapsing or refractory patients have a very poor survival despite salvage therapies. The PD-1/PD-L1 pathway plays a major role in peripheral tolerance and homeostasis by inhibiting T-cell activation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 15 publications
3
25
0
Order By: Relevance
“…Depending on the cut‐off levels used for positivity, previous studies on adult DLBCL indicated a wide range of 26%‐75% of patients to be PD‐L1‐positive . In studies including immunocompromised patients, similar to our patient cohort, the proportion of PD‐L1‐positive B‐cell lymphoma cases was rather comparable to that seen by us .…”
Section: Discussionsupporting
confidence: 88%
“…Depending on the cut‐off levels used for positivity, previous studies on adult DLBCL indicated a wide range of 26%‐75% of patients to be PD‐L1‐positive . In studies including immunocompromised patients, similar to our patient cohort, the proportion of PD‐L1‐positive B‐cell lymphoma cases was rather comparable to that seen by us .…”
Section: Discussionsupporting
confidence: 88%
“…In previous studies, high level of soluble PD-L1 in blood was an independent poor prognostic factor for OS in patients with systemic DLBCL. 36 Given the poor prognostic implication of tPD-L1 in PCNS-DLBCL observed in this study, it may deserve to investigate the prognostic significance of soluble PD-L1 in blood or cerebrospinal fluid in PCNS-DLBCL.…”
Section: Pd-1 Expression Is Induced By T-cell Receptor Signaling On Amentioning
confidence: 89%
“…Moreover, a soluble form of PD-L1 was detected in the plasma but not in the serum of peripheral blood from DLBCL patients, and its expression levels had no correlation with PD-L1 expression on tumors. Elevated soluble PD-L1 expression was found to be either associated 89,90 or not associated 95 with poorer prognosis.…”
Section: Pd-l1 Expression and Clinical Roles In B-cell Lymphomasmentioning
confidence: 95%
“…25,41,87 PD-L1 was shown to be expressed in 26% to 75% of DLBCL samples with PD-L1 1 cutoff $5% 61,87-89 and more frequently in ABC-DLBCL, 57,60,87,88 and tumor PD-L1 expression has been associated with either poor prognosis or no significant prognostic effect. 57,58,61,90 PDL1/ PDL2 amplifications are rare in DLBCL, and 9p24.1 copy gain was identified in only 6% to 19% of patients with DLBCL. 57,88,91 Another form of genetic alteration, disruption of the PDL1 39 untranslated region, was identified in 8% of DLBCL samples.…”
Section: Pd-l1 Expression and Clinical Roles In B-cell Lymphomasmentioning
confidence: 99%